2020
DOI: 10.1177/1751143720980273
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal brain monitoring following traumatic brain injury: A primer for intensive care practitioners

Abstract: Traumatic brain injury (TBI) is common and potentially devastating. Traditional examination-based patient monitoring following TBI may be inadequate for frontline clinicians to reduce secondary brain injury through individualized therapy. Multimodal neurologic monitoring (MMM) offers great potential for detecting early injury and improving outcomes. By assessing cerebral oxygenation, autoregulation and metabolism, clinicians may be able to understand neurophysiology during acute brain injury, and offer therapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…Despite traumatic brain injury (TBI) being a leading cause of death and disability worldwide [1], current guideline-based management, focused on intracranial pressure (ICP) and cerebral perfusion pressure (CPP), has resulted in limited recent improvements in outcome following moderate and severe TBI [2,3]. Interest has shifted towards personalized medicine-based strategies that leverage contemporary multimodal monitoring techniques [4,5]. Two methods that have come to the forefront are brain tissue oxygen tension (PbtO 2 ) and ICP-based cerebrovascular pressure reactivity monitoring [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite traumatic brain injury (TBI) being a leading cause of death and disability worldwide [1], current guideline-based management, focused on intracranial pressure (ICP) and cerebral perfusion pressure (CPP), has resulted in limited recent improvements in outcome following moderate and severe TBI [2,3]. Interest has shifted towards personalized medicine-based strategies that leverage contemporary multimodal monitoring techniques [4,5]. Two methods that have come to the forefront are brain tissue oxygen tension (PbtO 2 ) and ICP-based cerebrovascular pressure reactivity monitoring [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…TBI treatment based on MMM-derived optimal cerebral perfusion has demonstrated improved clinical outcomes, especially in older patients who may have reduced autoregulatory capacity [81]. PRx allows for real-time measurement of cerebrovascular autoregulation [82] and may help to predict the need for surgical intervention in severe TBI [83][84][85]. Measurement of brain oxygenation parameters such as PbtO2 allows for rapid implementation of theraputic interventions to correct cerebral hypoxia [82,86], and measurement of PbtO2 and ICP in the BOOST-II trial was suggested to improve secondary injury after TBI demonstrating the potential effect of such early interventions [87].…”
Section: Multimodal Neuromonitoringmentioning
confidence: 99%
“…PRx allows for real-time measurement of cerebrovascular autoregulation [82] and may help to predict the need for surgical intervention in severe TBI [83][84][85]. Measurement of brain oxygenation parameters such as PbtO2 allows for rapid implementation of theraputic interventions to correct cerebral hypoxia [82,86], and measurement of PbtO2 and ICP in the BOOST-II trial was suggested to improve secondary injury after TBI demonstrating the potential effect of such early interventions [87]. Measurement of PbtO2, CPP and arterial oxygen saturation has been used to guide treatment of cerebral hypoxia in severe TBI, helping to uncover physiologic states that may lead to impaired brain oxygen metabolism [88].…”
Section: Multimodal Neuromonitoringmentioning
confidence: 99%
“…It is recognized that a “normal” PbtO 2 can be greater than 15–20 mmHg and lower values may indicate cerebral hypoxia and are associated with a greater lactate/glucose ratio and increased glycerol levels. However, there is no universal consensus on the threshold at with tissue injury occurs ( Casault et al, 2020 ).…”
Section: Neuromonitoring To Personalize Tbi Therapymentioning
confidence: 99%